Challenges and control mechanism for development on highland and steep slope: The case of Klang Valley - Alias, A.; Ali, A.S. (Construction Research Institute of Malaysia, 2016)
Development in highland areas carries a high risk of erosion and an increased risk of landslides both during and after construction. Since 1990, more than 13 cases of highland development incidents in the Klang Valley have been reported in newspapers, of which a few involved deaths of people. Hence, this paper discusses the issues and challenges of land development in highland and steep slope areas. The study also shows the effect of control mechanisms on the challenges identified in highland development. The quantitative survey adopted in this study was based on a framework developed from literature reviews. 200 questionnaires were distributed to relevant government agencies and developers. Of those, 157 found to be useful for data analysis. SPSS version 18.0 was used as the main tool for the data analyses. From the study, five dimensions of issues surrounding highland development were identified: planning, environmental, economic, social, and land development. Two main control mechanisms were also identified, namely the One Stop Centre (OSC) and the sustainable development approach. The associative test revealed that there were two significant relationships between control mechanisms and the challenges of highland development, which indicates the effectiveness of these mechanisms in addressing current problems.